APPLICATION OF THE ASSURE MODEL AND SELF-DIRECTED LEARNING TO IMPROVE ENGLISH SPEAKING SKILLS FOR STUDENTS AT UNIVERSITAS HARAPAN MEDAN - Ningsih, Ayu Melati; Kristiana, Vera; Yuliana, Yayuk (PHILOLOGY Journal of English Language and Literature, 2025)
This research aims to analyze the application of the ASSURE model and Self-Directed Learning in improving English speaking skills for students at Universitas Harapan Medan. The ASSURE model, which involves analyzing student needs, setting objectives, selecting media and materials, and evaluation, is integrated with the Self-Directed Learning approach, which encourages students to actively manage their own learning process. This research uses an experimental method with a pre-test and post-test design to measure changes in students' English- speaking abilities after the implementation of both models. The research results show that the implementation of the ASSURE model and Self-Directed Learning significantly improves students' English-speaking skills. Students become more confident and able to express their ideas more fluently and accurately. Thus, both approaches have proven effective in improving English speaking skills among students at Universitas Harapan Medan.